(untitled) (Pulse, 2026)
Laryngeal cancer is the second most common type of head & neck malignancies. This cancer commonly spreads to regional lymph nodes and distant metastasis is rare. Liver metastasis rarely occurs without evidence of lung or bone involvement. We report a case with a history of squamous cell carcinoma of the larynx treated by definitive radiotherapy nine years earlier, had developed isolated liver metastases on 18F-fluorodeoxy- D-glucose Positron Emission Tomography-Computed Tomography (FDG PET-CT). Pulse Volume 17, Issue 2 2025; 30-33